Evaluation of PDAM Performance Using Dynamic Models - Helmi Kristiawan; Nieke Karnaningroem; Maritha Nilam Kusuma (Institut Teknologi Adhi Tama Surabaya, 2020)
the Regional Government is the fulfillment of basic needs of daily drinking water. However, the service by PDAM is still not optimal. It can be seen from the PDAM's performance that was “unhealthy from year to year according to BPPSPAM data. Some of the research methods used in analyzing PDAM performance are problem identification, identification of variables and conceptual models, dynamic model simulations, analysis and interpretation as well as drawing conclusions and suggestions. From the simulation result of dynamic models using Vensim PLE plus software, alternative scenarios were obtained, that will increase domestic water consumption and customer connections by 12.5% per year, increasing the repair and replacement of distribution piping systems and customer meters by 20% per year, and increasing rate to 15% per year.